2012
DOI: 10.1111/acps.12007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of psychoeducation on symptomatic and functional recovery in bipolar disorder

Abstract: Objective:  To evaluate the efficacy of psychoeducation in the symptomatic and functional recovery, and quality of life (QoL) in a sample of patients with bipolar disorder (BD).Method:  The sample comprised 55 patients with BD I and II in remission (Young Mania Rating Scale ≤6 and Hamilton Depression Rating Scale ≤7). Out‐patients were matched assigned to receive 16 sessions of psychoeducation [experimental group (EG)] or 16 sessions of placebo without psychoeducation [control group (CG)]. Groups were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 25 publications
1
56
0
3
Order By: Relevance
“…On the other hand, a systematic review carried out by the Cochrane Collaboration (Justo et al, 2007) concluded that there was a poor and mixed amount of evidence supporting the effectiveness of family oriented approaches for bipolar disorders, making impossible to draw firm conclusions about their role as additional treatment for these disorders. The results of the systematic review were confirmed by de Barros Pellegrinelli et al (2013) who reported that psychoeducation is ineffective in preventing mood episodes or improving functioning in bipolar patients. This apparent inconsistency is probably due to the fact that several different approaches are included under the label of "psychoeducation" (Lucksted et al, 2012), with several changes over the years (Colom, 2014;Fiorillo et al, 2013a).…”
mentioning
confidence: 62%
“…On the other hand, a systematic review carried out by the Cochrane Collaboration (Justo et al, 2007) concluded that there was a poor and mixed amount of evidence supporting the effectiveness of family oriented approaches for bipolar disorders, making impossible to draw firm conclusions about their role as additional treatment for these disorders. The results of the systematic review were confirmed by de Barros Pellegrinelli et al (2013) who reported that psychoeducation is ineffective in preventing mood episodes or improving functioning in bipolar patients. This apparent inconsistency is probably due to the fact that several different approaches are included under the label of "psychoeducation" (Lucksted et al, 2012), with several changes over the years (Colom, 2014;Fiorillo et al, 2013a).…”
mentioning
confidence: 62%
“…In contrast to these earlier trials, de Barros Pellegrinelli and colleagues (32) in Brazil found no advantage of the PE group (administered as a 16-rather than 21-session intervention) compared with TAU over a 1-year period. They found that on the HAM-D, both groups had increased depressive symptoms at endpoint (p=0.014) with no differences between groups.…”
Section: Resultsmentioning
confidence: 76%
“…In all but one trial (27), psychotherapy was administered as an adjunct to pharmacologic treatments. In most cases, the addition of psychotherapy to pharmacotherapy was associated with improved outcomes for bipolar disorder compared with the control condition [but for exceptions, see, Scott et al (28), Meyer and Hautzinger (29), Parikh et al (30), Crowe et al (31), and de Barros Pellegrinelli et al (32)]. Below we briefly describe individual and group models of psychotherapy tested for bipolar disorder and the evidence supporting their efficacy/effectiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O TB é uma condição psiquiátrica caracterizada por alterações de humor, com episódios maníacos/hipomaníacos e depressivos, sendo subdividido em TB tipo I e TB tipo II (APA, 2013). Esse diagnóstico pode comprometer as atividades do indivíduo, os relacionamentos interpessoais e principalmente a qualidade de vida (Mussi et al, 2013;Pellegrinelli et al, 2013).…”
Section: Introductionunclassified